Diffusion-weighted imaging in rectal carcinoma patients without and after chemoradiotherapy: a comparative study with histology - Bäuerle, Tobias; Seyler, L.; Münter, Marc; Jensen, Alexandra; Brand, Karsten; Maier-Hein, Klaus H.; Kopp-Schneider, Annette; Schüssler, Max; Schlemmer, Heinz-Peter; Stieltjes, Bram; Ganten, Maria-Katharina (European journal of radiology, 2013)
Diffusion-weighted imaging (DWI) can be used to quantitatively assess functional parameters in rectal carcinoma that are relevant for prognosis and treatment response assessment. However, there is no consensus on the histopathological background underlying the findings derived from DWI. The aim of this study was to perform a comparison of DWI and histologic parameters in two groups of rectal carcinoma patients without (n=12) and after (n=9) neoadjuvant chemoradiotherapy (CRT). The intravoxel incoherent motion (IVIM) model was used to calculate the diffusion coefficient D and the perfusion fraction f in rectal carcinoma, the adjacent rectum and fat in the two patient groups. Immunohistological analysis was performed to assess the cellularity, vascular area fraction and vessel diameter for comparison and correlation. Out of 36 correlations between parameters from DWI and histology, four were found to be significant. In rectal carcinoma of patients without CRT, the diffusion D and the perfusion f correlated with the vascular area fraction, respectively, which could not be found in the group of patients who received CRT. Further correlations were found for the rectum and fat. Histological evaluation revealed significant differences between the tissues on the microscopic level concerning the cellular and vascular environment that influence diffusion and perfusion. In conclusion, DWI produces valuable biomarkers for diffusion and perfusion in rectal carcinoma and adjacent tissues that are highly dependent of the underlying cellular microenvironment influenced by structural and functional changes as well as the administered treatment, and consequently can be beyond histological ascertainability.